Competitividade do Brasil na transição energética global com a implantação do HUB de hidrogênio verde do Ceará: um estudo à luz da teoria da hélice quíntupla - Benvindo, Janaina dos Santos (2024)
Climate change emerges as the central challenge for the future of sustainable development. The Quintuple Helix is a strategy to address the climate crisis, integrating ecology, knowledge, and innovation, and generating synergies between economy, society, and democracy. In this context, transitioning to more sustainable energy sources is imperative, and green hydrogen (H2V) emerges as a promising alternative. Its impact on the energy trade is significant, potentially causing future shifts in energy power centers. Regions like the Middle East, known for their oil production, may face new competitors. Countries with abundant natural resources, such as Brazil, have the potential to lead H2V production, impacting the global economy and politics. An initiative in this regard is the implementation of an H2V hub in the state of Ceará. Thus, this study aims to investigate how the implementation of the Ceará H2V Hub can enhance Brazil's competitiveness in the global energy transition, from the perspective of the Quintuple Helix Model. Using a qualitative, theoretical-empirical approach, interviews were conducted with representatives from the five helices: academia, government, industry, society, and the environment. The data were analyzed through discursive textual analysis, using the IRaMuTeQ software. The main results revealed a predominance of the Triple Helix model in the context of the formation of the Ceará H2V Hub, highlighting challenges in adopting the Quintuple Helix. The lack of societal engagement and limited consideration of environmental aspects are obstacles to achieving the mentioned model. Brazil faces a mixed scenario of progress and challenges in preparing for the energy transition, focusing on H2V. Although there is growing awareness of environmental sustainability and investments in human capital, especially in Ceará, infrastructure and innovation represent barriers to this market. Furthermore, there are obstacles in the sustainability of the financial sector, such as the lack of long-term financing for H2V projects. Finally, despite the abundance of natural resources, technological dependence may compromise Brazil's competitiveness, even with the implementation of the Hub, underscoring the need for investments in research, development, and innovation to strengthen national technologies and reduce dependence on foreign technologies